Interpreting Islam, Modernity, and Women's Rights in Pakistan - Weiss, Anita M.; SpringerLink (Online service). (New York : Palgrave Macmillan US, 2014)
This book analyzes how different constituencies within Pakistan are grappling with interpreting and redefining Muslim women's rights in contemporary society.
Keywords: Political science; Culture -- Study and teaching; Political philosophy; Social sciences -- Philosophy; Sociology; Political sociology; Sex (Psychology).; Gender expression; Gender identity; Political Science and International Relations; Gender Studies; Cultural and Media Studies, general; Political Sociology; Political Philosophy; Social Philosophy